Survival Time Analysis of Multiple Myeloma Patients using Type 1 Censored Exponential Distribution Parameter Estimation - Wahyu Subekti, Cahya Arsyika; Nilasari, Inas; Syarif, Devi Mufidah; Syahzaqi, Idrus; Kurniawan, Ardi (Universitas Muhammadiyah Mataram, 2025)
Multiple myeloma is a type of blood cancer that attacks plasma cells in the bone marrow and affects the immune system. This study analyzes the survival time of patients with multiple myeloma using Type 1 censored exponential distributed parameter estimation. The data, consisting of 47 patients (35 uncensored and 12 censored), were tested for exponential distribution fit using the Anderson-Darling test, yielding a p-value of 0.495, confirming the suitability of the exponential model. The maximum likelihood estimation method was applied, resulting in a parameter estimate (θ ̂) of approximately 54.028 days, representing the mean survival time. Hypothesis testing and confidence intervals were conducted, with the 95% confidence interval for θ_0 ranging between 32 and 53 days. The findings suggest that the exponential distribution effectively models the survival data, providing insights into patient survival trends and supporting clinical decision-making.